Preparation method of super-lubricating anti-fog flexible porous electrode
By constructing an organic gel layer on the flexible electrode, combining carbon nanotubes and polydimethylsiloxane, the problem of degradation of electrical performance of the flexible electrode in the wet environment is solved, and superlubricated anti-fog performance is achieved, ensuring stable and sensitive electrical signal output.
Patent Information
- Application Number
- CN202510075394.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-15
AI Technical Summary
During the wear process, the flexible electrode is affected by the human sweat and external wetting environment, resulting in a decrease in electrical performance and the inability to accurately obtain physiological signals.
The melamine sponge is used as a porous matrix, and is constructed through electrostatic modification and multi-layer structure, combining carbon nanotubes and polydimethylsiloxane, and finally an organic gel layer is constructed on the surface of the electrode to achieve hydrophobic, anti-fog and anti-immersion effects.
The ultra-lubricating and anti-fog performance of flexible porous electrodes is achieved, which avoids the infiltration and corrosion of condensation droplets on the electrode surface, ensures stable and sensitive electrical signal output, and improves the service life of the equipment.
Smart Images

Figure CN119823444A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of porous electrodes and relates to a method for preparing a super-lubricating anti-fog flexible porous electrode. Background Art
[0002] The functional integration of wearable electronic devices is an important basis for the intelligentization of products. As an important component of wearable electronic devices, the intelligent development of the functions of flexible electrodes is of extraordinary significance. Flexible electrodes are often used to measure physiological, psychological and motor signals of the human body in the wearable field. However, these flexible electrodes need to be in contact with the human body and the external environment for a long time during the wearing process, and their electrical properties will be disturbed by human sweat and the external wetting environment. For example, even if the electrode has good waterproof performance, it will be wetted when facing tiny droplets in the environment, making it impossible to accurately obtain physiological signals such as heart rate, blood pressure, EEG, etc. Therefore, the preparation of super-lubricating anti-fog flexible porous electrodes is very important.
[0003] In order to solve the problem of small droplets wetting the surface of materials, the existing technology is to achieve waterproofing, water collection and self-driving of droplets by constructing surface lubricating coatings, material array structures and multi-level composite structures, thereby avoiding the wetting of materials by droplets of various volumes. Among them, the strict structure and low surface energy of the lubricating coating make it play an important role in the technology of achieving good waterproof performance of flexible electrode materials.
[0004] At present, the development of lubricating coatings has long been committed to the fields of drag reduction and corrosion prevention, and its development in wearable devices is still in its early stages. The research on lubricating coatings based on the surface interface of electrode materials is a relatively cutting-edge technical field. Although the lubricating coating can effectively prevent water infiltration after being applied to the surface interface of flexible electrodes, the flexible electrode will be subject to force and have structural deformation problems during the application process, and the lubricating fluid is very easy to leak from the material during the structural deformation process, thereby reducing the durability of the lubricating interface. Therefore, it is very critical to regulate the interface microstructure of the lubricating coating to achieve the synergistic effect of conductive properties and anti-infiltration properties. In addition, improving the interface bonding strength of the lubricating coating on the electrode surface is also the key to preventing lubricating fluid leakage. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a super-lubricating anti-fog flexible porous electrode, wherein the prepared porous electrode has the characteristics of being hydrophobic, anti-fog and anti-infiltration.
[0006] The technical solution adopted by the present invention is a method for preparing a super-lubricating anti-fog flexible porous electrode, which is specifically implemented according to the following steps: Step 1, immersing the melamine sponge in a polyethyleneimine solution, taking it out after standing, and drying it to obtain a positively charged MF; Step 2, immersing the positively charged MF in an anhydrous ethanol suspension of carbon nanotubes, taking it out after standing, and drying it to complete an electrostatic self-assembly; Step 3, repeating steps 1-2 multiple times to prepare a multi-layer MWCNTs / MF porous electrode; Step 4, immersing the multilayer MWCNTs / MF porous electrode in an ethyl acetate solution of polydimethylsiloxane, taking it out after standing, and drying it to obtain a PDMS / MWCNTs / MF porous electrode; Step 5, immersing the PDMS / MWCNTs / MF porous electrode in dimethyl silicone oil, letting it stand and taking it out, then alternately centrifuging and ultraviolet irradiating it multiple times to obtain a dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode.
[0007] The present invention is also characterized in that: In step 1, the pore size of the melamine sponge is 50 μm-500 μm, and the concentration of the polyethyleneimine solution is 0.1-0.5 mg / mL.
[0008] In step 1, the standing time is 10-30 minutes and the drying temperature is 70°C.
[0009] In step 2, the concentration of the carbon nanotube / anhydrous ethanol suspension is 0.5-5 mg / mL, the standing time is 10-30 min, and the drying temperature is 70°C.
[0010] In step 4, the model of polydimethylsiloxane is DC184, and the mass fraction of polydimethylsiloxane / ethyl acetate solution is 0.5%-2%.
[0011] In step 4, the standing time is 0.15h-4h, and the drying temperature is 40°C-120°C.
[0012] In step 5, the viscosity of the dimethyl silicone oil is 1000 cst-30000 cst.
[0013] In step 5, after the electrode is taken out from the dimethyl silicone oil, it is first centrifuged to separate excess dimethyl silicone oil, the centrifugal speed is 4000r / min-6000r / min, and the centrifugal time is 8-12min; then it is irradiated with an ultraviolet lamp, the power of the ultraviolet lamp is 80W, the band is 405nm, and the irradiation time is 8-12 min; the centrifugation and ultraviolet irradiation are repeated alternately for 8-10 times each.
[0014] The beneficial effects of the present invention are: The method of the present invention uses melamine sponge (MF) as a porous matrix, and uses polyethyleneimine to positively modify it, so that the porous MF can better adsorb multi-walled carbon nanotubes; the multi-walled carbon nanotubes are electrostatically assembled on the positively modified porous MF, so that the porous MF has excellent conductivity, and the prepared porous electrode is hydrophobized with polydimethylsiloxane of model DC184, so that the porous MF has good hydrophobicity; dimethyl silicone oil is used to construct an organic gel layer as a lubricating coating on the surface of the porous electrode through centrifugation and ultraviolet light irradiation. The lubricating coating has excellent hydrophobicity, anti-fog performance and dew drop adhesion performance, and realizes waterproof, anti-fog, fog collection and anti-infiltration of the surface of the flexible porous electrode, which can avoid the infiltration and corrosion of condensed droplets on the electrode surface, and realize stable and sensitive electrical signal output. In addition, the design of the organic gel layer can enhance the interface bonding strength and avoid the leakage of the lubricating fluid affecting its performance. In the long-term use process, it can reduce maintenance costs and improve the overall service life of the equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a flow chart of the method of the present invention; Figure 2 1 is a SEM morphology of the porous electrode prepared in Example 1 of the present invention, wherein Figure a is the SEM morphology of the multilayer MWCNTs / MF porous electrode, Figure b is the SEM morphology of the PDMS / MWCNTs / MF porous electrode, and Figure c is the SEM morphology of the dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode; Figure 3 This is a comparison diagram of the surface states of the electrodes prepared in Example 1 of the present invention and Comparative Example 1 after being wetted with water; Figure 4 The current-time curves of the electrodes prepared in Example 1 and Comparative Example 1 of the present invention 30 seconds before and 30 seconds after infiltration; Figure 5 1 is the cyclic voltammetry test curve of the electrode prepared in Example 1 of the present invention before and after infiltration; Figure 6 This is the cyclic voltammetry test curve of the electrode prepared in Comparative Example 1 of the present invention before and after infiltration. DETAILED DESCRIPTION
[0016] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0017] The method for preparing the super-lubricating anti-fog flexible porous electrode of the present invention is specifically implemented according to the following steps: Step 1, electrostatic modification of melamine sponge (MF): Immerse MF with a pore size of 50 μm-500 μm in a polyethyleneimine (PEI) solution with a concentration of 0.1-0.5 mg / mL, let it stand for 10-30 minutes, then take it out and dry it at 70°C to obtain positively charged MF; Step 2, carbon nanomaterial self-assembly: The positively charged MF was immersed in a suspension of carbon nanotubes (MWCNTs) / anhydrous ethanol with a concentration of 0.5-5 mg / mL, and then taken out after standing for 10-30 minutes and dried at 70°C to complete an electrostatic self-assembly. Carbon nanomaterials can also choose highly conductive materials such as graphene and MXene.
[0018] Step 3, preparation of multilayer MWCNTs / MF porous electrode: Repeat steps 1-2 multiple times to prepare a multi-layer MWCNTs / MF porous electrode; Step 4, hydrophobic treatment: The multilayer MWCNTs / MF porous electrode was immersed in a polydimethylsiloxane (PDMS) / ethyl acetate solution with a mass fraction of 0.5%-2% for 0.15h-4h, and then taken out and dried at 40℃-120℃ to obtain a PDMS / MWCNTs / MF porous electrode; Among them, the model of polydimethylsiloxane is DC184 (A:B=10:1, volume ratio).
[0019] Step 5, organic gel layer construction: The PDMS / MWCNTs / MF porous electrode was immersed in dimethyl silicone oil with a viscosity of 1000cst-30000cst. After taking it out, a centrifuge was used to separate the excess dimethyl silicone oil. The centrifugal speed was 4000r / min-6000r / min, and the centrifugal time was 8-12min. Then, it was irradiated with an ultraviolet lamp (UV). The power of the ultraviolet lamp was 80W, the band was 405nm, and the irradiation time was 8-12min. Centrifugation and UV irradiation were repeated alternately for 8-10 times each to obtain a super-lubricating, anti-fog, and flexible dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode.
[0020] Example 1 Step 1, electrostatic modification of MF: MF (1 cm × 1 cm × 0.3 cm) with a pore size of 50 μm-500 μm was immersed in a 0.1 mg / mL PEI solution, allowed to stand for 10 min, then taken out and dried in an oven at 70 °C to obtain pretreated MF.
[0021] Step 2, carbon nanotube self-assembly: the pretreated MF was immersed in a 1 mg / mL MWCNTs / anhydrous ethanol suspension, left to stand for 30 min, then taken out and dried in an oven at 70° C. to complete an electrostatic self-assembly.
[0022] Step 3, repeat steps 1-2 three times to prepare a multilayer MWCNTs / MF porous electrode material.
[0023] Step 4, hydrophobic treatment: immerse the MWCNTs / MF porous electrode in a 1.5% by mass polydimethylsiloxane DC184 / ethyl acetate solution for 10 min, take it out and dry it in an oven at 100°C to obtain a PDMS / MWCNTs / MF porous electrode.
[0024] Step 5, construction of the organic gel layer: immerse the PDMS / MWCNTs / MF porous electrode in dimethyl silicone oil with a viscosity of 1000cst-30000cst, with an adsorption amount of 0.323g. Take out the electrode and use a centrifuge (4000r / min, 10min) to peel off excess dimethyl silicone oil. The treated electrode is then irradiated with an ultraviolet lamp (80W, 405nm) for 10min. Alternate centrifugation and ultraviolet irradiation for 10 times each to obtain a dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode.
[0025] like Figure 2 As shown in the figure, the SEM morphologies of the multilayer MWCNTs / MF porous electrode, PDMS / MWCNTs / MF porous electrode and dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode prepared in this embodiment at different magnifications are shown. It can be seen that in Figure a, the multi-walled carbon nanotubes are tightly attached to the surface and pores of the melamine sponge, so that the porous MF has excellent conductivity. In Figure b, polydimethylsiloxane (DC184) covers the multi-walled carbon nanotubes, so that the porous MF has good hydrophobicity. In Figure c, dimethyl silicone oil almost completely covers the surface of the porous electrode, which can enable the porous electrode to resist the intrusion of fog and achieve a super-lubricating effect.
[0026] Example 2 Step 1, electrostatic modification of MF: MF (1 cm × 1 cm × 0.3 cm) with a pore size of 50 μm-500 μm was immersed in a 0.5 mg / mL PEI solution, allowed to stand for 20 min, then taken out and dried in an oven at 70 °C to obtain pretreated MF.
[0027] Step 2, carbon nanotube self-assembly: the pretreated MF was immersed in a 3 mg / mL MWCNTs / anhydrous ethanol suspension, allowed to stand for 10 min, taken out, and dried in an oven at 70° C. to complete an electrostatic self-assembly.
[0028] Step 3, repeat steps 1-2 three times to prepare a multilayer MWCNTs / MF porous electrode material.
[0029] Step 4, hydrophobic treatment: immerse the MWCNTs / MF porous electrode in a 2% by mass polydimethylsiloxane DC184 / ethyl acetate solution for 30 minutes, take it out and dry it in an oven at 120°C to obtain a PDMS / MWCNTs / MF porous electrode.
[0030] Step 5, construction of the organic gel layer: immerse the PDMS / MWCNTs / MF porous electrode in dimethyl silicone oil with a viscosity of 1000cst-30000cst, with an adsorption amount of 0.323g. Take out the electrode and use a centrifuge (4000r / min, 12min) to peel off excess dimethyl silicone oil. The treated electrode is then irradiated with an ultraviolet lamp (80W, 405nm) for 8min. Alternate centrifugation and ultraviolet irradiation for 10 times each to obtain a dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode.
[0031] Example 3 Step 1, electrostatic modification of MF: MF (1 cm × 1 cm × 0.3 cm) with a pore size of 50 μm-500 μm was immersed in a 0.5 mg / mL PEI solution, allowed to stand for 30 min, then taken out and dried in an oven at 70 °C to obtain pretreated MF.
[0032] Step 2, carbon nanotube self-assembly: the pretreated MF was immersed in a 0.5 mg / mL MWCNTs / anhydrous ethanol suspension, left to stand for 30 min, then taken out and dried in an oven at 70° C. to complete an electrostatic self-assembly.
[0033] Step 3, repeat steps 1-2 three times to prepare a multilayer MWCNTs / MF porous electrode material.
[0034] Step 4, hydrophobic treatment: immerse the MWCNTs / MF porous electrode in a 0.5% by mass polydimethylsiloxane DC184 / ethyl acetate solution for 4 h, take it out and dry it in an oven at 40°C to obtain a PDMS / MWCNTs / MF porous electrode.
[0035] Step 5, construction of the organic gel layer: immerse the PDMS / MWCNTs / MF porous electrode in dimethyl silicone oil with a viscosity of 1000cst-30000cst, with an adsorption amount of 0.323g. Take out the electrode and use a centrifuge (4000r / min, 10min) to peel off excess dimethyl silicone oil. The treated electrode is then irradiated with an ultraviolet lamp (80W, 405nm) for 12min. Alternate centrifugation and ultraviolet irradiation for 10 times each to obtain a dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode.
[0036] Example 4 Step 1, electrostatic modification of MF: MF (1 cm × 1 cm × 0.3 cm) with a pore size of 50 μm-500 μm was immersed in a 0.3 mg / mL PEI solution, allowed to stand for 30 min, then taken out and dried in an oven at 70 °C to obtain pretreated MF.
[0037] Step 2, carbon nanotube self-assembly: the pretreated MF was immersed in a 5 mg / mL MWCNTs / anhydrous ethanol suspension, allowed to stand for 10 min, taken out, and dried in an oven at 70° C. to complete an electrostatic self-assembly.
[0038] Step 3, repeat steps 1-2 five times to prepare a multilayer MWCNTs / MF porous electrode material.
[0039] Step 4, hydrophobic treatment: immerse the MWCNTs / MF porous electrode in a 1% by mass polydimethylsiloxane DC184 / ethyl acetate solution for 1 h, take it out and dry it in an oven at 80°C to obtain a PDMS / MWCNTs / MF porous electrode.
[0040] Step 5, construction of the organic gel layer: immerse the PDMS / MWCNTs / MF porous electrode in dimethyl silicone oil with a viscosity of 1000cst-30000cst, with an adsorption amount of 0.354g. Take out the electrode and use a centrifuge (5000r / min, 10min) to peel off excess dimethyl silicone oil. The treated electrode is then irradiated with an ultraviolet lamp (80W, 405nm) for 10min. Alternate centrifugation and ultraviolet irradiation for 8 times each to obtain a dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode.
[0041] Example 5 Step 1, electrostatic modification of MF: MF (1 cm × 1 cm × 0.3 cm) with a pore size of 50 μm-500 μm was immersed in a 0.1 mg / mL PEI solution, allowed to stand for 10 min, then taken out and dried in an oven at 70 °C to obtain pretreated MF.
[0042] Step 2, carbon nanotube self-assembly: the pretreated MF was immersed in a 1 mg / mL MWCNTs / anhydrous ethanol suspension, left to stand for 20 min, then taken out and dried in an oven at 70° C. to complete an electrostatic self-assembly.
[0043] Step 3, repeat steps 1-2 three times to prepare a multilayer MWCNTs / MF porous electrode material.
[0044] Step 4, hydrophobic treatment: immerse the MWCNTs / MF porous electrode in a 0.5% by mass polydimethylsiloxane DC184 / ethyl acetate solution for 3 h, take it out and dry it in an oven at 100° C. to obtain a PDMS / MWCNTs / MF porous electrode.
[0045] Step 5, construction of the organic gel layer: immerse the PDMS / MWCNTs / MF porous electrode in dimethyl silicone oil with a viscosity of 1000cst-30000cst, with an adsorption amount of 0.323g. Take out the electrode and use a centrifuge (4000r / min, 12min) to peel off excess dimethyl silicone oil. The treated electrode is then irradiated with an ultraviolet lamp (80W, 405nm) for 10min. Alternate centrifugation and ultraviolet irradiation for 10 times each to obtain a dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode.
[0046] Example 6 Step 1, electrostatic modification of MF: MF (1 cm × 1 cm × 0.3 cm) with a pore size of 50 μm-500 μm was immersed in a 0.2 mg / mL PEI solution, allowed to stand for 15 min, then taken out and dried in an oven at 70 °C to obtain pretreated MF.
[0047] Step 2, carbon nanotube self-assembly: the pretreated MF was immersed in a 2 mg / mL MWCNTs / anhydrous ethanol suspension, left to stand for 15 min, then taken out and dried in an oven at 70° C. to complete an electrostatic self-assembly.
[0048] Step 3, repeat steps 1-2 four times to prepare a multilayer MWCNTs / MF porous electrode material.
[0049] Step 4, hydrophobic treatment: immerse the MWCNTs / MF porous electrode in a 2% by mass polydimethylsiloxane DC184 / ethyl acetate solution for 20 min, take it out and dry it in an oven at 90°C to obtain a PDMS / MWCNTs / MF porous electrode.
[0050] Step 5, construction of the organic gel layer: immerse the PDMS / MWCNTs / MF porous electrode in dimethyl silicone oil with a viscosity of 1000cst-30000cst, with an adsorption amount of 0.305g. Take out the electrode and use a centrifuge (6000r / min, 8min) to peel off excess dimethyl silicone oil. The treated electrode is then irradiated with an ultraviolet lamp (80W, 405nm) for 8min. Alternate centrifugation and ultraviolet irradiation for 9 times each to obtain a dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode.
[0051] Comparative Example 1 This comparative example is basically the same as Example 1, except that the organic gel layer is not constructed, that is, step 5 is not performed.
[0052] Comparative Example 2 This comparative example is basically the same as Example 1, except that in step 5, the PDMS / MWCNTs / MF porous electrode is immersed in dimethyl silicone oil with a viscosity of 1000 cst-30000 cst for a period of time, the adsorption amount is 0.323 g, and the subsequent centrifugation and ultraviolet irradiation steps are not performed.
[0053] Comparative Example 3 This comparative example is basically the same as Example 1, except that in step 5, centrifugation and ultraviolet irradiation are alternately performed 5 times each, specifically: Step 5, construction of the organic gel layer: immerse the PDMS / MWCNTs / MF porous electrode in dimethyl silicone oil with a viscosity of 1000cst-30000cst, with an adsorption amount of 0.323g. Take out the electrode and use a centrifuge (4000r / min, 10min) to peel off excess dimethyl silicone oil. The treated electrode is then irradiated with an ultraviolet lamp (80W, 405nm) for 10min. Alternate centrifugation and ultraviolet irradiation for 5 times each to obtain a porous electrode.
[0054] After the porous electrodes prepared in Example 1 and Comparative Examples 1-3 were immersed in a droplet environment for 30 seconds, their electrochemical properties were tested using an electrochemical workstation, and the voltage was set to 1V during the test.
[0055] like Figure 3 As shown, it is a comparison diagram of the state of water droplets on the electrode surface after the electrodes prepared in Example 1 and Comparative Example 1 are infiltrated in a droplet environment. It can be seen that the standing state of water droplets on the electrode prepared in Example 1 is better than that in Comparative Example 1, which proves that the electrode prepared in Example 1 has excellent hydrophobicity after being infiltrated in a droplet environment.
[0056] like Figure 4As shown in the figure, the current-time curves of the electrodes prepared in Example 1 and Comparative Example 1 before and after immersion for 30 seconds and 30 seconds, it can be seen that before and after immersion, the current of the electrode prepared in Example 1 remains unchanged, and the resistance remains basically unchanged; while the current of the electrode prepared in Comparative Example 1 increases from 2.00×10 -3 A rapidly decreased to 1.90×10 -3 A, resistance increased by 26Ω after infiltration.
[0057] In addition, the test results show that the current of the electrode prepared in Comparative Example 2 is from 5.95×10 -4 A rapidly decreased to 4.67×10 - 4 A, the resistance increased by 461Ω after infiltration; the current of the electrode prepared in Comparative Example 3 increased from 6.10×10 -4 A rapidly decreases to 5.92e×10 -4 A, The resistance of the electrode increases by 50Ω after wetting.
[0058] like Figure 5 and Figure 6 As shown, they are cyclic voltammetry test curves of the electrodes prepared in Example 1 and Comparative Example 1 before and after infiltration. It can be seen that the current and resistance of the electrode prepared in Example 1 remain basically unchanged before and after infiltration in the droplet environment, and the current and resistance of the electrode prepared in Comparative Example 1 change significantly before and after infiltration in the droplet environment, which proves that the electrode prepared in Example 1 has excellent anti-fog properties.
[0059] In summary, by comparing Example 1 and Comparative Example 1, it can be seen that the method of the present invention greatly improves the waterproof and anti-fogging performance of the electrode by constructing an organic gel layer on the surface of the porous electrode.
[0060] Comparing Example 1 and Comparative Example 2, it can be seen that in the process of constructing the organic gel layer, the steps of centrifugation and ultraviolet irradiation are indispensable. Centrifugation can throw out the excess dimethyl silicone oil inside the porous electrode, reducing the impact of dimethyl silicone oil on the conductive properties of the porous electrode; while ultraviolet irradiation can make the dimethyl silicone oil penetrate from the inside of the porous electrode to the surface and form a thin film on the surface to prevent the fog from eroding the electrode. Because the hydrogen atoms on the methyl groups arranged outwards of the dimethyl silicone oil have a repulsive effect on the hydrogen atoms in the water, water and hydrophilic oxygen cannot approach, the surface energy of the coating is reduced, the hydrophobicity of the porous electrode is increased, and the porous electrode achieves super-lubricating performance.
[0061] In addition, by comparing Example 1 with Comparative Example 3, it can be seen that during the construction of the organic gel layer, the number of alternating cycles of centrifugation and ultraviolet irradiation must reach 8-10 times respectively. If it is less than this number, a good waterproof and anti-fog effect cannot be achieved.
Claims
1. A method for preparing a super-lubricating anti-fog flexible porous electrode, characterized in that: Follow the steps below to implement it: Step 1, immersing the melamine sponge in a polyethyleneimine solution, taking it out after standing, and drying it to obtain a positively charged MF; Step 2, immersing the positively charged MF in an anhydrous ethanol suspension of carbon nanotubes, taking it out after standing, and drying it to complete an electrostatic self-assembly; Step 3, repeating steps 1-2 multiple times to prepare a multi-layer MWCNTs / MF porous electrode; Step 4, immersing the multilayer MWCNTs / MF porous electrode in an ethyl acetate solution of polydimethylsiloxane, taking it out after standing, and drying it to obtain a PDMS / MWCNTs / MF porous electrode; Step 5, immersing the PDMS / MWCNTs / MF porous electrode in dimethyl silicone oil, letting it stand and taking it out, then alternately centrifuging and ultraviolet irradiating it multiple times to obtain a dimethyl silicone oil / PDMS / MWCNTs / MF porous electrode.
2. The method for preparing the super-lubricating anti-fog flexible porous electrode according to claim 1, characterized in that: In step 1, the pore size of the melamine sponge is 50 μm-500 μm, and the concentration of the polyethyleneimine solution is 0.1-0.5 mg / mL.
3. The method for preparing the super-lubricating anti-fog flexible porous electrode according to claim 1, characterized in that: In step 1, the standing time is 10-30 minutes and the drying temperature is 70°C.
4. The method for preparing the super-lubricating anti-fog flexible porous electrode according to claim 1, characterized in that: In step 2, the concentration of the carbon nanotube / anhydrous ethanol suspension is 0.5-5 mg / mL, the standing time is 10-30 min, and the drying temperature is 70°C.
5. The method for preparing the super-lubricating anti-fog flexible porous electrode according to claim 1, characterized in that: In step 4, the model of the polydimethylsiloxane is DC184, and the mass fraction of the polydimethylsiloxane / ethyl acetate solution is 0.5%-2%.
6. The method for preparing the super-lubricating anti-fog flexible porous electrode according to claim 1, characterized in that: In step 4, the standing time is 0.15h-4h, and the drying temperature is 40°C-120°C.
7. The method for preparing the super-lubricating anti-fog flexible porous electrode according to claim 1, characterized in that: In step 5, the viscosity of the dimethyl silicone oil is 1000cst-30000cst.
8. The method for preparing the super-lubricating anti-fog flexible porous electrode according to claim 1, characterized in that: In step 5, after the electrode is taken out from the dimethyl silicone oil, it is first centrifuged to separate excess dimethyl silicone oil, the centrifugal speed is 4000r / min-6000r / min, and the centrifugal time is 8-12min; then it is irradiated with an ultraviolet lamp, the power of the ultraviolet lamp is 80W, the band is 405nm, and the irradiation time is 8-12 min; the centrifugation and ultraviolet irradiation are repeated alternately for 8-10 times each.